The Local Batak Color in the Longa Novel by Nestor Rico Tambunan - Pertiwi, Bela Hastya; Doyin, Mukh.; Edy Nugroho, Yusro (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was conducted to describe the local Batak colors and their functions contained in the novel Longa by Nestor Rico Tambunan. There are two approaches used, namely a theoretical approach using the sociology of literature approach with the theory of culture studies. Then the methodological approach uses a qualitative descriptive approach. The data in this study are the forms of cultural color contained in the words, sentences, and expressions in Longa's novel which are suspected of containing story facts about the characters and traditional Batak cultural background. While the data source used in this study is the novel Longa by Nestor Rico Tambunan. The data collection method uses the heuristic method, and the analysis method uses the hermeneutic method. There are five cultural elements contained in the novel, namely 1) religious systems and religious ceremonies; 2) social systems and organizations; 3) knowledge system; 4) language; and 5) art.